Health status of and health-care provision to asylum seekers in Germany: protocol for a systematic review and evidence mapping of empirical studies - Tunkl, Christine; Mohsenpour, Amir; Joos, Stefanie; Bozorgmehr, Kayvan (Systematic Reviews, 2014)
There are more than 100,000 asylum seekers registered in Germany, who are granted limited access to health services. This study aims to provide a systematic overview of the empirical literature on the health status of and health-care provision to asylum seekers in Germany in order to consolidate knowledge, avoid scientific redundance, and identify research gaps.
Gesehen am 20.10.2020